Kajian Kualitas dan Kuantitas Karya Sastra Berdasarkan Kebijakan Pengembangan Sastra Pemerintah Indonesia - Saputro, Dimas Eko; Pasopati, Rommel Utungga; Napitupulu, Johanes Claudio Perdana; Wijaya, Kusuma (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Literary works are the identity of a nation, including Indonesian literary works. Indonesia, with its diverse culture, has created many literary works that are already global, and are born from regional writers and progressively become widespread in the world of literature. This article examines how the effects of Indonesian government’s literary development influence the quality and quantity of literary works. Through qualitative method, this paper analyzes that the government’s policy plays an important role because it contains plans that are arranged and realized by the experts for the important benefit of society. It may also improve the quality and quantity of literary works from authors’ and publishers’ sides. In conclusion, such policy should be pushed forward to build an awareness of the cultural forms and to preserve Indonesian culture to the international scope.